Impact of Increased Prosthetic Mass on Gait Symmetry in Dysvascular Transfemoral Amputees: A Randomized Prospective Double-Blind Crossover Trial. Issue 2 (April 2015) - Moylan, Beverly; Paner, Ruby; Pauley, Tim; Dilkas, Steven; Devlin, Michael
Abstract : ABSTRACT: Introduction: The trend in the prosthetic industry is toward the use of lightweight prostheses. Lighter components are more expensive; however, a lighter prosthesis does not improve the metabolic cost of ambulation for a transfemoral amputee. One study showed more than half of participants preferred a weighted prosthesis, with no adverse effect on self-selected walking speed. The purpose of this study was to determine the impact of increased prosthetic mass on gait symmetry, as well as weight preference, in dysvascular transfemoral amputees when comparing across three mass conditions. Methods: A single-center, prospective, double-blind, crossover trial design with randomization of testing conditions was used. Ten unilateral transfemoral amputees, from peripheral vascular disease (PVD), had visually seemingly identical weights of 180 g (placebo mass), 726 g, and 1633 g added to their prosthesis. Gait asymmetry was assessed using the GAITRite walkway, and subject preference was recorded. Results: Repeated-measures analysis of variance (ANOVA) of direct GAITRite spatiotemporal measures showed no differences across prosthetic mass conditions. However, there was a statistically significant difference in the calculated secondary measure of degree of asymmetry (DoA) in step width, with the heaviest condition imparting greatest symmetry. Ninety percent of subjects preferred the weighted prostheses. Conclusions: Short-term increases in prosthetic mass do not adversely impact direct spatiotemporal gait measures in dysvascular transfemoral amputees. However, the heaviest mass brought gait width closer to parity, which is the ideal outcome. In addition, most subjects preferred a heavier prosthesis. These results do not support a shift toward lighter prostheses in dysvascular transfemoral amputees.